Implications of overlap in tariff policy on waste management costs in Italian municipalities - Giacomo Di Foggia; Ioannis Kostakis; Konstadinos Abeliotis; Massimo Beccarello (Environmental Research Communications)
In today’s race toward a more circular economy, optimization of tariff design is important for minimizing the environmental impact and costs of municipal waste management. This study examines the overlap of an incentive-based tariff method and the unit pricing system. We address whether this overlap impacts the effectiveness and efficiency of waste management in Italian municipalities. Based on a panel data sample for 5,512 municipalities from 2016 to 2022, a generalized method of moments estimation was employed for a linear dynamic panel model. The results suggest that there is room for optimizing their overlap under certain circumstances—specifically, when the availability of waste treatment facilities is adequate and the percentage of separate waste collection is high. The interaction between the percentage of separate collection and the incentive tariff method contributed to cost reduction, confirming the need for consistency and compatibility of a tariff scheme with circular economy objectives. The effective adoption of both tools, as well as other actions such as information campaigns and service delivery improvements, can promote waste sorting and investment in management facilities. The results provide insights for policymakers seeking to design more effective and efficient policy measures aimed at maximizing environmental effectiveness, in accordance with the polluter-pays principle, and minimizing costs.